The Icelandic translation of the Bath Adolescent Pain - Parental Impact Questionnaire (BAP-PIQ) : preliminary psychometric properties of multidimensional measures for parents of adolescents with chronic pain to assess the impact on parents - Halla Ruth Halldórsdóttir 1987- (2016)
In Iceland there are no measures available that capture, in one scale, the multidimensional negative effects of having a child or adolescents with chronic pain has on their parents. The Bath Adolescents Pain Questionnaire - Parental Impact Questionnaire (BAP-PIQ) was developed to assess these multidimensional effects by including domains of anxiety, child related catastrophizing, depression, partner relationship, leisure functioning, parental behavior, self-blame and helplessness, and parental strain. The goal of this study was, therefore to translate BAP-PIQ into Icelandic and to evaluate the psychometric properties both of BAP-PIQ and the Pediatric Quality of Life Inventory-Family Impact module (PedsQL-FIM). Participants were 69 parents (mostly mothers) of adolescents that had been experiencing chronic pain for the previous three months. The parents answered online the BAP-PIQ and PedsQL-FIM as well as the following questionnaires which were used to examine construct validity: The Depression, Anxiety and Stress Scales (DASS), The Pediatric Quality of Life Inventory Parent proxy-report (PedsQL) and The Pain Catastrophizing Scale for parents (PCS-P). Hringiðan Háskólinn í Reykjavík